Pollen Donor Position and Climate Factor Affecting Fruit Production of Nutmeg - Susi Purwiyanti; NFN Sudarsono; Yudiwanti Wahyu Endro Kusumo; Otih Rostiana (Buletin Penelitian Tanaman Rempah dan Obat, 2018)
The quality and quantity of nutmeg fruit, seed and mace can be improved through managing fruit and seed production.  Fruit development was affected by climate, flower initiation and pollination process. This study aimed to determine the correlation between climate, position, distance of pollen donor to female nutmeg trees, and the ratio of female and male trees to nutmeg yield.  The study was conducted at the nutmeg germplasm collection garden at Cicurug (550 m asl), Sukabumi, tested 295 nutmeg trees from 27 locations in Indonesia. Data production of female trees was based on 2005-2017 data. All nutmeg trees were mapped using the GPS Garmin 76c5x.  Tree sex was determined by male or female flowers domination in each tree. Correlation of the climate factors and production was analyzed using Pearson Correlation. The distance, position and the proportion of female to male trees were evalated by t-test at 5% level.  Ratio of female and male trees to produce high yield was 4 : 1. Rainfall (280-430 mm/month) and temperature (24 - 25o C)   during  the  pollination  period  (8-7  months  before  harvesting)  were positively correlated with production by 57.9 % and 82.3 %. The position and distance of pollen donors to female trees had no effect on production.  However, the distance between pollen donors and female trees above 15 m produced an average production equal to 15 m. The number of trees around tree samples had no effect on nutmeg production, but light intensity at 61,425-88,480 lux absorbed by trees could enhance the yield.  Nutmeg required sunlight to penetrate plant canopy in order to induce fruit production.